Choosing Non-Subsidized Mortgage Financing for Bank Tabungan Negara Bogor Branch Customers with Brand Image as an Intervening Variable - Nitra Silvia (International Journal of Economics Accounting and Management, 2026)
This study aims to analyze the influence of product quality and price perception on the decision to choose non-subsidized mortgage financing from Bank BTN Bogor Branch, with brand image as a mediating variable. This research uses a quantitative approach with a survey method. Data was collected from 290 respondents who are customers or prospective customers of BTN Bogor Branch's Non-Subsidized Home Ownership Loans (KPR). The data was gathered using a Likert scale questionnaire. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The research results indicate that product quality has a positive and significant impact on brand image and purchasing decisions. Price perception is also proven to have a positive and significant influence on brand image and purchase decisions. In addition, brand image significantly influences purchase decisions. Brand image is also able to significantly mediate the influence of product quality and price perception on purchase decisions. This finding confirms that consumer perceptions of product quality and price not only have a direct influence but also shape brand image, which in turn strengthens consumer decisions in choosing BTN Non-Subsidized Mortgage financing.